Membrane Technology in Treatment of Coal Chemical Industry Saline Wastewater - Zhang, Yang; Zhou, Jun-Bo; Li, Jun-Zhan (Asian Journal of Chemistry, 2015)
For the wastewater recovery in coal chemical industry, the reverse osmosis + dish-tube reverse osmosis membrane separation technology was taken to concentrate the saline wastewater (the concentration of sodium sulfate was 2.5 %) after biological treatment. The experimental result showed that the concentration of sodium sulfate can reached 23 and 94.4 % of sodium sulfate was recovered. The recovery rate of primary reverse osmosis system and secondary dish-tube reverse osmosis system were 50 and 80 %, respectively, meanwhile, the sodium sulfate concentration of reverse osmosis and dish-tube reverse osmosis permeated water were 0.116 and 0.611 g/L severally. The chemical oxygen demand index were 4.5 and 23.96 mg/L as well. The study verified the application of membrane technology in the treatment of saline wastewater and it illustrated that the dish-tube reverse osmosisprocess can be used as further concentration process of saline wastewater.